A Thermodynamic Study of Adsorption 2-(4-Antipyriyl azo) Orcinol [APAO] on Zincoxide as Adsorbent - Nuha Abdul-Saheb Ridha (Journal of Global Pharma Technology, 2020)
We can remove Organic materials contaminated from their solutions in several methods, for examples the Adsorption. In this research was studies adsorption APAO which dissolved in 2.5% ethanol/water by the Zinc Oxide as adsorbent. The adsorption isotherms it was found similar to L4-shape according to Gilles classification. Also it studied the influence of adsorbent weight and adsorption time on removal% of APAO; it was 0.35gm best weight and 35 min. best time. The impact of changing the function of the acidic PH on removal% of APAO was found as follows (PH=4> PH=10> PH=7). The thermodynamic values were calculated (∆H, ∆G, ∆S) depending on changing temperature with concentration were (+24.74002KJ/mol, +9.4256KJ/mol, +51.390J/mol.K).